DiACL - Diachronic Atlas of Comparative Linguistics - Carling, Gerd (Lund University, 2017)
DiACL is an open access database with lexical and typological/morphosyntactic data for historical, comparative and phylogenetic linguistics. It contains data from 500 languages of 18 families, divided into three macro-areas: Eurasia, Pacific, and the Amazon. The database has the following content: 1) Lexical datasets with basic vocabularies (Swadesh lists), 2) Lexical datasets with culture vocabularies, focusing on subsistence system vocabulary, 3) Typological/morphosyntactic datasets including the main types Word Order, Alignment, and Nominal/ Verbal Morphology.
DiACL contains data from contemporary and historical languages, and, if possible, reconstructed languages. Data is derived from dictionaries, grammars, or by new fieldwork (in particular data from Caucasus and the Amazon). All data is sourced in scientifically reliable literature.

Purpose:

The aim of the database is to make datasets for evolutionary and comparative linguistics available open access. The datasets, which are comparative and complete, span over large geographic areas, containing data for typology/morphosyntax and lexicon (basic vocabulary and culture vocabulary). Datasets can be used to investigate spatio-temporal and linguistic comparative correlations.

Data has been compiled by analyzing grammars and dictionaries and by means of fieldwork. The population of data into the database is controlled by matrix documents, questionnaires and careful instructions, in order to creat complete and comparable dtasets. The process of population has been supervised by the database editor (Gerd Carling) and language experts for each language group.

Cite as:
Carling, Gerd (ed.) 2016/2017. Diachronic Atlas of Comparative Linguistics Online. (Available at: https://lundic.ht.lu.se/. Accessed on: z.).

Data from individual languages should preferably be quoted by their source:
NN, NN, NN, NN. Data set: x (basic vocabulary/culture vocabulary/typology), y (language). In: Carling, Gerd (ed.) 2016/2017. Diachronic Atlas of Comparative Linguistics Online. (Available at: https://lundic.ht.lu.se/. Accessed on: z.).

Diachronic Atlas of Comparative Linguistics är en databas med lexikal och typologisk/morfosyntaktisk data för historisk, komparativ och fylogenetisk lingvistik. Den innehåller data från 500 språk från 18 familjer, uppdelade på 3 makroområden: Eurasien, Stillahavsregionen och Sydamerika. Databasen har följande innehåll: 1) Lexikala dataset med basvokabulär, 2) Lexikala dataset med kulturvokabulärer, 3) Typologisk/morfosyntaktisk data, inkluderande huvudtyperna ordföljd, satssyntax, nominal och verbal morfologi. Databasen innehåller data från samtida och historiska språk och, om möjligt, även rekonstruerade språk. Data har samlats in från lexika, grammatikor och genom nytt fältarbete (i synnerhet från Kaukasus och Sydamerika). All data är källhänvisad till vetenskapligt tillförlitlig litteratur.

Syfte:

Databasens syfte är språkhistoriskt och evolutionärt och avser att göra bearbetad lingvistisk data, som kan användas för olika typer av analyser, öppet tillgänglig. De nedladdningsbara dataseten, som är jämförbara och kompletta, med data för typologi/morfosyntax och lexikon (bas- och kulturvokabulär) spänner över stora områden och kan därför användas till att göra sofistikerade och storskaliga analyser över geografiska och temporala korrelationer, baserade på samtida och historisk språklig data.

Data i databasen har samlats in genom analys av grammatikor, lexika och genom språkligt fältarbete. Datan har samlats in och matats in i databasen under kontollerade former, genom frågeformulär och matrisdokument, för att få kompletta och jämförbara dataset. Insamlandet har gjorts under översyn av databasens redaktör (Gerd Carling) och språkliga experter på varje område.

Citera som:
Carling, Gerd (ed.) 2016/2017. Diachronic Atlas of Comparative Linguistics Online. (Available at: https://lundic.ht.lu.se/. Accessed on: z.).

Data från enskilda språk bör helst citeras som:
NN, NN, NN, NN. Data set: x (basic vocabulary/culture vocabulary/typology), y (language). In: Carling, Gerd (ed.) 2016/2017. Diachronic Atlas of Comparative Linguistics Online. (Available at: https://lundic.ht.lu.se/. Accessed on: z.).
DiACL - Diachronic Atlas of Comparative Linguistics
Keywords: Philology; Filologi; linguistics; lingvistik; language documentation; språkdokumentation; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur